A New Approach to the Synthesis of Benzo[b]naphtho[2,3-b]furan-6,11-diones and 2-Benzyl-3-hydroxynaphthalene-1,4-diones - Barcia, Jose C.; Cruces, Jacobo; Salas, Cristian O.; Estévez, Juan C.; Cuellar, Mauricio A.; Tapia, Ricardo A.; Estévez, Ramón J. (SynOpen, 2017)
Here we describe modified syntheses of o-acetylbenzoic acids and o-acetylphenylacetic acids by Heck palladium-catalysed arylation of n-butyl vinyl ether with o-iodobenzoic acids or with o-iodophenylacetic acids, respectively. General syntheses of benzo[b]naphtho[2,3-b]furan-6,11-diones from o-acetylbenzoic acids and 2-benzyl-3-hydroxynaphthalene-1,4-diones from o-acetylphenylacetic acids are also reported.
Keywords: fused-ring systems; Heck reaction; quinones; palladium; heterocycles; halides; furans